Hydro-geology and Water Resources of Indus-Gangetic Basin: Comparative Analysis of Issues and Opportunities - Sharma, Bjarat R; Ambili, G K (Annals of Arid Zone, 2016)
This paper gives an overview of water resources, its availability and use, problems and constraints, the present and future challenges and the ensuing opportunities in water resource sp.ctor of one of the most populated river basins of the world; the Indus-Gangetic Basin. Large-scale development of water resources in the Indus Basin has led to the resource base being depleted, both in terms of quantity as well as quality. Well-developed surface irrigation systems in the Indus Basin tap most of the surface water available in the basin, leaving only 10% of the net runoff to the sea, whereas from Ganges Basin, the net runoff flowing to the sea is about 40%. Groundwater, which is expected to serve as buffer source to compensate for the reduced surface water availability, is also getting depleted. Energy and agricultural sector policies followed also favor large-scale exploitation of groundwater resources in the basin, which has led to water table decline and a reduction in environmental flows. In the Gangetic part of the basin, it is the economic water scarcity, which is more prominent. Equally important is the deterioration of water quality of Ganges River, especially when it flows along the plains accumulating municipal, industrial and domestic waste from the rapidly growing cities situated along its banks. Compounded with these issues is the role played by climate change. Since both Indus and Ganges Rivers are heavily dependent on snow and glacier melts, the streamflow in these rivers is highly sensitive to climate change. Recent years have witnessed some responses to the water scarcity problem in IG Basin in the form of popularization of resource conservation practices, growing high yielding short duration varieties of paddy, micro and precision irrigation and regulations to control groundwater use and management. The article presses the need for water resources in the basin to be managed in a conjunctive manner, considering rain water, surface water, soil water and groundwater in continuum. Considering the inter-linkage between groundwater extraction, energy and food policies, groundwater management strategies should have a focus on energy pricing, food pricing and procurement policies also. Nevertheless, devising long-term strategies on water resource management in the basin need not overlook the likely impacts that the changing climate is going to have on water resources. Key words: Indus-Gangetic Basin, Indus Basin Irrigation System, Bhakra Nangal Project, groundwater recharge, groundwater governance, arsenic contamination, floods and droughts.